LSD alters eyes‐closed functional connectivity within the early visual cortex in a retinotopic fashion. Issue 8 (29th April 2016) - Roseman, Leor; Sereno, Martin I.; Leech, Robert; Kaelen, Mendel; Orban, Csaba; McGonigle, John; Feilding, Amanda; Nutt, David J.; Carhart‐Harris, Robin L.
Abstract: The question of how spatially organized activity in the visual cortex behaves during eyes‐closed, lysergic acid diethylamide (LSD)‐induced "psychedelic imagery" (e.g., visions of geometric patterns and more complex phenomena) has never been empirically addressed, although it has been proposed that under psychedelics, with eyes‐closed, the brain may function "as if" there is visual input when there is none. In this work, resting‐state functional connectivity (RSFC) data was analyzed from 10 healthy subjects under the influence of LSD and, separately, placebo. It was suspected that eyes‐closed psychedelic imagery might involve transient local retinotopic activation, of the sort typically associated with visual stimulation. To test this, it was hypothesized that, under LSD, patches of the visual cortex with congruent retinotopic representations would show greater RSFC than incongruent patches. Using a retinotopic localizer performed during a nondrug baseline condition, nonadjacent patches of V1 and V3 that represent the vertical or the horizontal meridians of the visual field were identified. Subsequently, RSFC between V1 and V3 was measured with respect to these a priori identified patches. Consistent with our prior hypothesis, the difference between RSFC of patches with congruent retinotopic specificity (horizontal–horizontal and vertical–vertical) and those with incongruent specificity (horizontal–vertical and vertical–horizontal) increased significantly under LSD relative to placebo, suggesting that activity within the visual cortex becomes more dependent on its intrinsic retinotopic organization in the drug condition. This result may indicate that under LSD, with eyes‐closed, the early visual system behaves as if it were seeing spatially localized visual inputs. Hum Brain Mapp 37:3031–3040, 2016 . ©2016 Wiley Periodicals, Inc .